Pengembangan Kewirausahaan Dan Bantuan Sosial Di Yayasan Almani Kota Batam - Wahyudi Ilham (JURNAL KEKER WISATA, 2024)
This study examines the efforts in entrepreneurship development and social assistance conducted by the Almani Foundation in Batam City. The foundation's entrepreneurship development program includes skill training, business mentoring, and access to capital for local communities, especially youth and housewives. Additionally, the Almani Foundation provides various forms of social assistance such as free healthcare services, educational scholarships, and distribution of food packages to underprivileged families. The aim of these initiatives is to improve economic welfare, reduce poverty rates, and enhance the quality of life of the local community. The results of these programs show an increase in entrepreneurial skills, economic independence, and better access to basic services for the beneficiaries. With a sustainable approach and comprehensive support, the Almani Foundation significantly contributes to creating positive change in Batam City.